Tragfähigkeit mechanischer und geklebter Verbindungsmittel in Buchenfurnierschichtholz - Meyer, Nico (Karlsruher Berichte zum Ingenieurholzbau, 2021)
Laminated veneer lumber made of beech shows a three times higher tensile strength as glued laminated timber made from softwood. Due to the strength properties laminated veneer lumber made of beech is an ideal material for the realization of slender and wide‐span timber structures. In this study, the design and construction principles for economic connections are created.